Localization of Material Supply: A Literature Review - (:unkn) unknown (My University, 2017)
Tedarik zincirinin esnekliğini artıran ve maliyet azaltma tekniklerinden biri olarak görülen Malzeme Tedarikinde Yerlileştirme, günümüz küreselleşen dünyasında en son eğilimlerden biri haline gelmiştir. Son on yıla baktığımız zaman, hem akademisyenler hem de pratik uygulamacılar nazarında Yerlileştirmenin farkındalığı artmıştır. Bu makalenin amacı Yerlileştirmeyi etkileyen faktörleri önermek ve bu alanda uygulanan metotları ve güncel çalışmaları incelemektir. Çalışma Tedarik Zincirinde Yerlileştirme üzerine, özellikle de, Malzeme Tedarikinde Yerlileştirme üzerine yoğunlaşmıştır. Bununla birlikte, Satış Alanındaki Yerlileştirme konusundaki araştırmalar da incelenmiş ve tartışılmıştır. Bu çalışmanın literatüre katkısı, Malzeme Tedarikinde Yerlileştirme konusunda yapılan çalışmaların sektör, tip ve kullanılan metotların analizi noktasında olmaktadır. Ayrıca, Malzeme Tedarikinde Yerlileştirme noktasında yeni araştırma alanları da önerilmektedir

Localization of Material Supply which is considered as a cost reduction method and a strategy that increases the flexibility of the supply chain in the companies has become one of the most recent trends in our globalized world. The awareness of the Localization increased over the last decade within both academics and practitioners. The purpose of the article is to suggest the factors that affect Localization and review the recent studies of Localization and analyse the methods that have been used in this field. The paper focusses on Localization in Supply Chains, more specifically, Localization of Material Supply. However, the publications about Sales Localization according to Regional Culture are also reviewed and discussed. This review considering Localization of Material Supply contributes to the literature by analysing the sectors, types and methods. Moreover, new research directions for Localization of Material Supply are proposed
Malzeme Tedarikinde Yerlileştirme: Bir Literatür Araştırması